SOCIOCULTURAL PECULIARITIES OF ETHNOGRAPHIC WORDS IN THE POETIC WORKS OF AJINIYAZ - Р.К.; Н.М. (FAN va JAMIYAT, 2016)
The article deals with the issues of linguoculturology, one of the actual branches formed on the basis of interaction of language and culture. There have been analysed the sociocultural peculiarities of the special layer of the Karakalpak vocabulary as ethnographisms on the material of literary works of the famous Karakalpak poet of the XIX-th century Ajiniyaz. Ethnographisms reflect the culture, traditions and customs of the people. The investigation shows that ethnographisms in the works of the Karakalpak poet-classic reflect cutoms, traditions, moral and other norms of the period when the poet lived. The object of the study is ethnographisms connected with national games, clothes of people and such characteristic feature of the Karakalpak people as hospitality. The study of the ethnographisms in the poetic works shows their great significance for Karakalpak linguoculturology.